Molecular mechanism and role of microRNA‐93 in human cancers: A study based on bioinformatics analysis, meta‐analysis, and quantitative polymerase chain reaction validation. Issue 4 (2nd November 2018) - Gao, Yun; Deng, Kaifeng; Liu, Xuexiang; Dai, Meiyu; Chen, Xiaoli; Chen, Jifei; Chen, Jianming; Huang, Yujie; Dai, Shengming; Chen, Jingfan
Abstract: Introduction: Currently, studies have shown that microRNA‐93 (miR‐93) can be an oncogene or a tumor suppressor in different kinds of cancers. The role of miR‐93 in human cancers is inconsistent and the underlying mechanism on the aberrant expression of miR‐93 is complicated. Methods: We first conducted gene enrichment analysis to give insight into the prospective mechanism of miR‐93. Second, we performed a meta‐analysis to evaluate the clinical value of miR‐93. Finally, a validation test based on quantitative polymerase chain reaction (qPCR) was performed to further investigate the role of miR‐93 in pan‐cancer. Results: Gene Ontology (GO) enrichment analysis results showed that the target genes of miR‐93 were closely related to transcription, and MAPK1, RBBP7 and Smad7 became the hub genes. In the diagnostic meta‐analysis, the overall sensitivity, specificity, and area under the curve were 0.76 (0.64‐0.85), 0.82 (0.64‐0.92), and 0.85 (0.82‐0.88), respectively, which suggested that miR‐93 had excellent performance on the diagnosis for human cancers. In the prognostic meta‐analysis, dysregulated miR‐93 was found to be associated with poor OS in cancer patients. In the qPCR validation test, the serum levels of miR‐93 were upregulated in breast cancer, breast hyperplasia, lung cancer, chronic obstructive pulmonary disease, nasopharyngeal cancer, hepatocellular cancer, gastric ulcer, endometrial cancer, esophageal cancer, laryngeal cancer, and prostate cancer compared with healthy controls. Conclusions: miR‐93 could act as an effective diagnostic and prognostic factor for cancer patients. Its clinical value for cancer early diagnosis and survival prediction is promising. Abstract : The role of miR‐93 in human cancer is inconsistent and the underlying mechanism on the aberrant expression of miR‐93 is complicated. This study was conducted to resolve the above problems. In conclusion, this study suggests that miR‐93 could act as an effective diagnostic and prognostic factor for cancer patients.